High levels of circulating CD34+/VEGFR3+ lymphatic/vascular endothelial progenitor cells is correlated with lymph node metastasis in patients with epithelial ovarian cancer. Issue 7 (26th June 2013) - Qiu, Huiling; Cao, Lili; Wang, Dan; Xu, Huicheng; Liang, Zhiqing
Abstract Aim Lymph node metastasis is one of the predictive factors associated with poor prognosis of epithelial ovarian cancer. To clarify the role of CD34 and vascular endothelial growth factor receptor‐3‐positive (CD34+/VEGFR3+) lymphatic/vascular endothelial progenitor cells (LVEPC) in patients with lymph node metastasis and epithelial ovarian cancer progression, the levels of circulating CD34+/VEGFR3+ LVEPC in epithelial ovarian cancer patients were detected. We also tested the plasma protein levels of VEGF and stromal cell‐derived factor to find out their possible relationships with lymph node metastasis in our epithelial ovarian cancer cohort. Material and Methods Peripheral blood samples were collected from 54 patients diagnosed as epithelial ovarian cancer, and 31 normal samples as control. The circulating levels of LVEPC were carried out by flow cytometry, and blood protein levels of biomarkers were measured by enzyme‐linked immunosorbent assay (ELISA). Results The level of circulating LVEPC was significantly higher in patients with ovarian cancer compared with that of healthy controls. There was also a statistically significant correlation between LVEPC levels and surgical staging of epithelial ovarian cancer (P < 0.01). Conclusion The circulating levels of bone marrow‐derived LVEPC are significantly increased in epithelial ovarian cancer patients and these levels correlate with lymph node metastasis too.